Theoretical analysis of transmembrane potential of cells exposed to nanosecond pulsed electric field. (1st February 2017) - Lu, Wei; Wu, Ke; Hu, Xiangjun; Xie, Xiangdong; Ning, Jing; Wang, Changzhen; Zhou, Hongmei; Yang, Guoshan
Abstract: Purpose: Intracellular electroporation occurs when the cells are exposed to nanosecond pulsed electric field (nsPEF). It is believed the electroporation (formation and extension of pores on the membrane induced by external electric field) is affected significantly by the transmembrane potential. This paper analyzed transmembrane potential induced by nsPEF in the term of pulse frequency spectrum, aiming to provide a theoretical explanation to intracellular bio-effects. Methods: Based on the double-shelled spherical cell model, the frequency dependence of transmembrane potential was obtained by solving Laplace's equation, while the time course of transmembrane potential was obtained by a method combined with discrete Fourier transform and Laplace transform. First-order Debye equation was used to describe the dielectric relaxation of the cell medium. Results: Frequency-domain analysis showed that when the electric field frequency was higher than 10 5 Hz, the transmembrane potential on the organelle membrane (ΔΦo ) was increasing to exceed the transmembrane potential on the cellular membrane (ΔΦc ). In the time-domain analysis, transmembrane potentials induced by four nsPEF (short trapezoid, long trapezoid, bipolar and sine shapes) with the same field strength were compared with each other. It showed that ΔΦo is obviously larger than ΔΦc if the curve of the normalized frequency spectrum of the pulse is more similar with the curve of normalized ΔΦo in frequency domain. Pulses with major frequency components higher than 10 8 Hz lead to both small ΔΦo and ΔΦc . This may explain why high power pulsed microwave lead to unobvious bio-effects of cells than nsPEF with trapezoid form. Conclusion: Through the pulse frequency spectrum it is clearer to understand the relationship between nsPEF and the transmembrane potential.